Riwayat KEK dan anemia pada ibu hamil tidak berhubungan dengan kejadian stunting pada anak usia 6-23 bulan di Kecamatan Sedayu, Bantul, Yogyakarta - Kristiana Tri Warsini; Hamam Hadi; Detty Siti Nurdiati (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2016)
ABSTRACTBackground: Quality of human resource was built since human being was in the womb. Pregnant mother’s health had signifi cant impact on fetus. Pregnant mother’s with anemia and CED would surely have significant impact on the fetus in their womb because it would make low birth weight. If a child with low birth weight can not catch up grow, it was highly possible that they would suffer from stunting. Objectives: The aim of this study was to identify the relationship between nutritional status of pregnant mother with stunting in children 6-23 age month in Sedayu, Bantul, Yogyakarta.Methods: It was observational study with case-control design. The number of samples were 252 children aged 6-23 months. All of stunting children aged 6-23 months in Sedayu subdistrict were selected as samples. Cases and controls samples were matching based on age. Data were collected using structured questionnaire to fi nd out the identity of the children aged 6-23 month, identity of respondents, the nutritional status of the children aged 6-23 month, the history of nutritional status of the pregnant mothers’ and sociodemographic. Anthropometric measurement used microtoise to fi nd out parent’s height, infantometer to find out children length, semi-quantitative food frequency questionnaire (SQ-FFQ) and food models were used as instrument. The data was analyzed using univariate analysis, bivariate analysis with chisquaretest, and multivariate analysis with multiple logistic regression.Results: The bivariate analysis showed that anemic history during pregnancy was the risk factor of stunting, but it was not statistically signifi cant (p=0.13, OR:1.5, 95% CI:0.85-2.73). The CED history during pregnancy was not the risk factor of the stunting incident (p=0.23, OR:0.7, 95% CI:0.37-1.31). Other factors related to the stunting incidence were mother’s height (p=0.01, OR:2.04, 95% CI:1.14-3.65), the history of low birth weight (p=0.03, OR:3.03, 95% CI:1.09-8.33), and food insecurity (p=0.04, OR:2.7, 95% CI:1.04-7.00). The multivariate analysis showed that mother’s height was correlated with the stunting incidence in Sedayu subdistrict.Conclusion: Factors that influence the incidence of stunting in children aged 6-23 month were pregnant mother with anemia, history of low birth weight, food insecurity, and stunted mother. Stunted mother was associated with the incidence of stunting. KEYWORDS: anemia, CED, growth disorder, pregnant women, risk factorsABSTRAKLatar belakang: Kualitas sumber daya manusia terbentuk sejak dalam kandungan. Kesehatan ibu saat hamil akan sangat mempengaruhi kesehatan janin yang dikandungnya. Ibu hamil yang anemia dan menderita kekurangan energi kronis (KEK) tentu akan mempengaruhi kesehatan janin yang dikandungnya, karena akan menyebabkan bayi lahir dengan berat yang rendah. Bila tidak bisa tumbuh kejar, bayi BBLR kemungkinan besar akan menderita stunting. Tujuan: Untuk mengetahui hubungan antara status gizi ibu saat hamil dengan kejadian stunting pada anak usia 6-23 bulan di Kecamatan Sedayu, Kabupaten Bantul.Metode: Penelitian ini merupakan penelitian observasional dengan desain case-control. Jumlah sampel penelitian sebanyak 252 anak berusia 6-23 bulan yang berasal dari 4 desa di Kecamatan Sedayu. Semua anak stunting usia 6-23 bulan diambil sebagai sampel, dengan matching umur kasus dan kontrol. Pengambilan data menggunakan kuesioner terstruktur untuk mengetahui identitas anak usia 6-23 bulan, identitas responden, status gizi anak usia 6-23 bulan, riwayat status gizi ibu saat hamil, dan data sosiodemografi. Pengukuran antropometri terhadap tinggi badan orang tua dengan microtoise dan panjang badan anak dengan infantometer serta untuk SQ-FFQ menggunakan food model. Data dianalisis dengan menggunakan analisis univariat (deskriptif), bivariat (chi-square), dan multivariat (regresi logistik).Hasil: Hasil bivariat menunjukkan riwayat anemia saat hamil merupakan faktor risiko terjadinya stunting tetapi secara statistik tidak signifikan (p=0,13, OR=1,5, 95%CI=0,85-2,73). Riwayat KEK saat hamil bukan faktor risiko terhadap kejadian stunting (p=0,23, OR=0,7, 95% CI=0,37-1,31). Faktor lain yang berhubungandengan kejadian stunting adalah tinggi badan ibu (p=0,01, OR=2,04, 95% CI=1,14-3,65), riwayat BBLR (p=0,03, OR=3,03, 95% CI=1,09-8,33), dan rawan pangan (p=0,04, OR=2,7, 95% CI=1,04-7,00). Hasil analisis multivariat adalah tinggi badan ibu berhubungan dengan kejadian stunting di Kecamatan Sedayu, Bantul, Yogyakarta.Kesimpulan: Faktor yang mempengaruhi kejadian stunting adalah ibu hamil yang menderita anemia, mempunyai riwayat BBLR, rumah tangga rawan pangan dan tinggi badan ibu yang kurang. Pada analisis multivariat yang berhubungan dengan kejadian stunting adalah tinggi badan ibu yang kurang. KATA KUNCI: anemia, KEK, stunting, ibu hamil, faktor risiko